2006
DOI: 10.2109/jcersj.114.1069
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviour of Silicon Nitride Ceramics in Aqueous Solutions

Abstract: Silicon nitride ceramics are used under conditions were high strength, hardness and wear resistant is necessary. The increasing use of Si 3 N 4 -ceramics as ceramic ball bearings and valves in chemical apparatus demand an understanding of the relations between microstructure and corrosion behaviour of silicon nitride ceramics in different environments. The stability of the ceramics against corrosion in acids and bases is mostly controlled by the stability of the grain boundary. Therefore, the influence of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…In this case, a media temperature change of just 30 K is sufficient to realize the different behaviors. A detailed discussion of the corrosion equation is given in the literature (Herrmann & Schilm, 2009;Herrmann, Schilm, Hermel, & Michaelis, 2006;Schilm, 2004;Schilm, Gruner, Herrmann, & Michael, 2006;Seipel & Nickel, 2003;Herrmann, 2013).…”
Section: Basic Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, a media temperature change of just 30 K is sufficient to realize the different behaviors. A detailed discussion of the corrosion equation is given in the literature (Herrmann & Schilm, 2009;Herrmann, Schilm, Hermel, & Michaelis, 2006;Schilm, 2004;Schilm, Gruner, Herrmann, & Michael, 2006;Seipel & Nickel, 2003;Herrmann, 2013).…”
Section: Basic Processesmentioning
confidence: 99%
“…Because of their different additive contents and processing/sintering, the ceramics have different grain boundary phase amounts and compositions. Studies of the corrosion resistance of Si 3 N 4 materials revealed a strong relationship between the stability of the grain boundary and the corrosion resistance of the ceramic material (Galuskova et al, 2011b;Herrmann & Schilm, 2009;Herrmann et al, 2006;Herrmann, 2005;Herrmann, 2012;Kitaoka et al, 1994;Kleebe et al, 1993;Nagae, Koyama, et al, 2006;Sato Figure 14 Potential effect of corrosion on the integrity of zirconia components (after Chevalier et al, 2009Chevalier et al, ). et al, 1988aChevalier et al, , 1988bSato et al, 1992;Schilm et al, 2003;Schilm et al, 2004a;Schilm et al, 2006;Schilm et al, 2007;Schilm, 2004;Seipel & Nickel, 2003;Shimada & Sato, 1989;Somiya, 2001).…”
Section: Corrosion Of Different Ceramics In Aqueous Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different Y 2 O 3 / Al 2 O 3 containing silicon nitride ceramics with amorphous grain boundaries exhibit varying degrees of corrosion-resistance, even to acids. 34 Aluminum implantation into raw silicon nitride is a valid strategy to control material oxidation that is mediated by sodium. 35 The beneficial role of aluminum is in surface modification of the ceramic, so that sodium-accelerated oxidation processes can be reversed.…”
Section: Materials Stability Of Silicon Nitridementioning
confidence: 99%